Barriers for the adoption of Smart Home products in the German and UK market - Höllriegel, Isabella; Tyll, Ladislav; Srivastava, Mohit; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
Digitalization has a huge impact on human life, up to a point where components in households are interconnected and enabled to communicate with each other through IoT technology, automating every-day tasks previously executed by humans. The market for such Smart Homes is expected to grow significantly in the next years, however, the UK and Germany show a lower utilization rate on household basis than the United States or Northern European countries. Throughout this thesis, application areas and device categories are identified, IoT and AI are put into context and the UK and German Smart Home markets are analyzed. In an empirical study, it is verified that age, location and ownership status influence consumers’ attitude towards the Smart Home concept and that data security concerns are identified as the main barrier, preventing prospective customers to adopt Smart Home technology.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses